Emergence of Community Structure in the Adaptive Social Networks (Communications in Computational Physics, 2010)
In this paper, we propose a simple model of opinion dynamics to constructsocial networks, based on the algorithm of link rewiring of local attachment (RLA)and global attachment (RGA). Generality, the system does reach a steady state whereall individuals' opinion and the complex network structure are fixed. The RGA enhancesthe ability of consensus of opinion formation. Furthermore, by tuning a modelparameter p, which governs the proportion of RLA and RGA, we find the formationof hierarchical structure in the social networks for p > pc. Here, pc is related to thecomplex network size N and the minimal coordination number 2K. The model also reproducesmany features of large social networks, including the "weak links" property.